Pemberdayaan Masyarakat Melalui Implementasi Pusat Kegiatan Belajar Masyarakat (PKBM) Surya Alam untuk Meningkatkan Ketrampilan Menjahit di Kabupaten Demak. - Teguh Imam Rahayu; Is Solikhatun; Umi Ma’rifatun (Universitas 17 Agustus 1945, 2024)
The times and the Covid-19 pandemic have contributed to increasingly declining economic conditions. Due to income inequality and high levels of new unemployment, many people are unable to meet their living needs. Empowerment is expected to help people acquire the skills, knowledge and mental attitudes needed to improve their quality of life. PKBM Surya Alam is one of the non-formal educational institutions in Demak Regency, which has various superior programs to empower the community, including pursuing Packages B and C, and several skills and skills programs, such as computers, electronics and sewing. In Demak Regency, especially young women or housewives who are still productive, tend to like sewing. There are several garment industries that require many female workers. Opportunities for entrepreneurship or working in the garment industry are greater for those who are skilled at sewing. This can help meet living needs and reduce the unemployment rate, especially for women. This research aims to find out: (1) How Surya Alam PKBM is implemented in Community Empowerment in Demak Regency, and (2) What efforts are made by Surya Alam PPKBM in Community Empowerment in Demak Regency. To collect data, this research used interviews and observations in a descriptive qualitative approach. The research results include: (1) The implementation of PKBM Surya Alam to improve sewing skills in Demak Regency was generally carried out well, although not yet optimal. There are still aspects that need to be improved, and (2) PKBM Surya Alam has provided services to the community in obtaining non-formal education, either regularly or through community empowerment from the Demak Government, especially sewing training.